Call Me Captain : A Memoir of a Woman at Sea - Scott, Susan, 1948- (Book collections on Project MUSE., 2014)
Writer and marine biologist Susan Scott had an enviable existence--a home in Hawai'i, a prized 37-foot sailboat and exciting international adventures, all shared with her physician husband Craig in a marriage so intimate they called it the "Twinship." Yet, when her menopausal hormones raged and Craig grew preoccupied with Ironman triathlon training, this perfect life ended. Once blessed with well-being, love, humor, and sharing, the Twinship exploded with fights, silence, accusations, and failed counseling. Shell-shocked, Susan sought solace in the one thing that always gave her joy: marine wildlife. She overhauled the couple's neglected boat and, with a male friend nearly half her age, sailed away. Except it wasn't that easy; Susan had always relied on Craig to make the sailing decisions and Alex, her young first mate, was a sailing novice. Call Me Captain follows Susan as she leaves everything behind--or tries to-- and sails to spectacular but isolated Palmyra Atoll to work as a volunteer biologist. Susan helps rescue baby sea turtles, bands seabirds, and corrals ten-pound coconut crabs that look like Godzillas with knife-blade claws. She determinedly repairs her sailboat, skippers it through terrifying storms, and to her surprise, finds she and Craig are falling in love all over again. This time the two rediscover one another via satellite phone--Susan calling from her tiny floating speck in the middle of the Pacific Ocean to Craig in his hospital emergency room on Oahu. Susan writes with passion about swimming with manta rays, kayaking with sharks, and sailing with whales and dolphins. In those passages, she shows ways these magnificent animals guided her through the journey of a lifetime. Her memoir of self-discovery is a romance, a rousing sea tale, and a personal account of nature's power to put life in perspective